2012
DOI: 10.4317/medoral.17313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of systemic diseases among patients requesting dental consultation in the public and private systems

Abstract: Objectives: To determine the prevalence and aetiology of systemic disease among patients requesting dental treatment in public and private practice. Study Design: A retrospective analysis was performed of the medical histories of 2000 patients requesting dental treatment during the year 2009. One thousand patients came from the Fontiñas Primary Care Oral and Dental Health Unit of the Galician Health Service (SERGAS), Spain, and the other thousand from a private clinic; both clinics were situated in Santiago de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
1
16
1
5
Order By: Relevance
“…2 Fernández-Feijoo et al, revealed the prevalence of systemic diseases 35.2% in the public system and 28.1% in the private system at Santiago de Compostela, Galicia, Spain. 3 In the survey of Netherlands, prevalence reported was 28.2%. 4 Umino et al, reported 64.2% prevalence of one or more medically compromised conditions in elderly Japanese dental patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…2 Fernández-Feijoo et al, revealed the prevalence of systemic diseases 35.2% in the public system and 28.1% in the private system at Santiago de Compostela, Galicia, Spain. 3 In the survey of Netherlands, prevalence reported was 28.2%. 4 Umino et al, reported 64.2% prevalence of one or more medically compromised conditions in elderly Japanese dental patients.…”
Section: Discussionmentioning
confidence: 98%
“…Patients, on several medications for their systemic diseases can directly or indirectly have impact on dental treatment. 2,3 Every dentist must have necessary skills to distinguish these co-morbid medical conditions which are related to their dental treatment. 4 People usually do not find any relation between their systemic and dental health, so they are reluctant to report their past medical history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4,5,7,11) It has been well proven that taking a complete and comprehensive clinical history by the dentist is necessary before dental treatments. (13) Thus, changing the treatment process of oral-dental illnesses is necessary to provide a better and safer treatment and to prevent potential interference with the stability of the patient's systemic health and drug consumption. (1,3,12,14) Considering the relatively high prevalence of systemic diseases, the importance of patient management, treatment planning, and treatment outcomes as well as the consequences of lack of knowledge in this regard, the lack of similarity of the reported prevalence in various studies, changes in the frequency of diseases over time, and also the lack of investigation in this regard during the last 10 years at the Dental Branch of Islamic Azad University of Tehran, we decided to determine the prevalence of systemic diseases among the patients referring to this university during 2016-17 in order to have accurate, new, and valid statistics of various systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a dentist visiting 2000 adult patients, is expected to meet at least 130 patients with chronic obstructive pulmonary disease, 100 patients with peptic ulcer disease, 220 patients with chronic renal failure, 100 patients taking corticosteroids with the possibility of adrenal suppression, and 3-4 patients with epilepsy. (4)(5)(6) Patients who have their first dental visit must consult with specialists in order to clarify different aspects of their general health status including the ones which are of ambiguity for the dentist upon checking the background or performing physical examination. (7)(8) Medical consultation is scientifically and legally considered as an important step in planning dental treatment for patients with systemic problems.…”
Section: Introductionmentioning
confidence: 99%